Constipation as a Rare Cause of Ventriculoperitoneal Shunt Dysfunction: A Case Report - Mete, Mesut; Selçuki, Mehmet (Journal of Pediatric Neurology, 2020)
Ventriculoperitoneal shunt (VPS) insertion is a common neurosurgical procedure for the treatment of hydrocephalus. Constipation can play an important role in shunt failure either by mechanically blocking drainage from the peritoneal end of the VPS catheter or by increasing intra-abdominal pressure. The present report describes a 2-year-old boy with shunt-dependent hydrocephalus who presented with signs of shunt dysfunction. Medical history with detailed physical examination determined the constipation. Before shunt revision, a pediatric fleet enema was administered to possibly relieve the constipation and he had good evacuation of the bowel contents. Following the enema, his continuous crying resolved and ultimately disappeared within a few hours. Brain computed tomography scans performed 4 days later showed a reduction in ventricular size.
Keywords: constipation; hydrocephalus; ventriculoperitoneal shunt